ANALYSIS OF LOSS WATER ON PIPE DISTRIBUTION â€NON REVENUE WATER (NRW)â€ NETWORK PDAM SURYA SEMBADA CITY OF SURABAYA WITH CAUSAL LOOP DIAGRAM (CLD): ANALYSIS OF LOSS WATER ON PIPE DISTRIBUTION â€NON REVENUE WATER (NRW)â€ NETWORK PDAM SURYA SEMBADA CITY OF SURABAYA WITH CAUSAL LOOP DIAGRAM (CLD) - Yanatra Budi Pramana (UNIPA PRESS, 2018)
Water is an important supporting factor in humanlife. The problem of clean water in an area is managed by Perusahaan Daerah Air Minum (PDAM) Surabaya. PDAM Surya Sembada as a water management company in Surabaya is expected to be able to distributethe needs of clean water, however, in the distribution network, sometimes experiencing problems that cause water is not fully channeled to the customer, to overcome this problem, the Causal Loop Diagram approach is used to identify the cause of the water loss,after knowing these factors, we have been made model with Causal Loop model,to calculate the water loss that occurred, in PDAM Surya Sembada Surabaya especially DMA 109 using Infrastructure Leakage Index (ILI) method. The Causal Loop Diagram approach, various causes of water loss include: physical water loss caused by reservoir leakage, transmission line leakage and distribution pipeline leakage; non physical water loss caused by meter fault, wild connection and water theft. Based on the data obtained, obtained NRW value at DMA 109 of 439.455.72 m3 / year or by 25% with a loss of 329.591.8 m3 / year. Service pipe leakage up to the customer meter is 1.757.822.8 m3 / year.